The Psychological Impact of Students as Witnesses to Bullying in Islamic Boarding Schools: A Phenomenological Study - Eka Malfasari; Junaiti Sahar; Novy Helena Catharina Daulima (Universitas STRADA Indonesia, 2025)
Background: bullying is a problem that never ages in school. Bullying continues to occur in schools. Currently, only the victims and perpetrators are being looked at a lot regarding the psychological impact they face. However, witnesses to bullying also experienced negative impacts due to the bullying, including for students at Islamic boarding schools who faced their friends 24 hours a day. Purpose: this study aims to explore the psychological impact of bullying witnesses on students in Islamic boarding schools. Methods: This research is a qualitative study with a phenomenological approach. The number of participants was five students who were selected using snowball sampling, with the criteria of being students who had witnessed bullying at an Islamic boarding school. Data were collected through in-depth interviews and field notes. The interviews were transcribed verbatim, and the data were analyzed using thematic analysis based on Colaizzi’s method. The process involved extracting significant statements, formulating meanings, clustering themes, and validating the findings with participants to ensure credibility. Results: this study produced 5 themes, namely the emotional reaction of bullying witnesses, feelings of guilt, sense of responsibility, coping mechanisms, and prevention strategies. Conclusion: bullying has a psychological impact on students, so it is necessary to intervene efforts that must be given so that they do not fall to further stages.